2004
DOI: 10.1097/01.asn.0000133531.43177.21
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte Flattening and Disorder of Glomerular Basement Membrane Are Associated with Splitting of Dystroglycan-Matrix Interaction

Abstract: Abstract. The transmembrane component of the dystroglycan complex, a heterodimer of ␣-and ␤-dystroglycan, was recently localized at the basal cell membrane domain of podocytes, and it was speculated that it serves as a device of the podocyte for maintaining the complex podocyte foot process architecture, and for regulating the exact position of its ligands, the matrix proteins laminin and agrin, in the glomerular basement membrane (GBM). The redistribution of dystroglycan in two experimental rat models of foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 45 publications
6
34
0
Order By: Relevance
“…The membrane staining observed in normal glomeruli likely reflects the expression of DG in podocytes. 30 On the other hand, the significance of the cytoplasmic staining observed in tubuli is not clear and it cannot be excluded that it is due to a non-specific cross-reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The membrane staining observed in normal glomeruli likely reflects the expression of DG in podocytes. 30 On the other hand, the significance of the cytoplasmic staining observed in tubuli is not clear and it cannot be excluded that it is due to a non-specific cross-reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the DG complex undergoes changes in human glomerular diseases in which flattening of foot processes is directly associated with dissociation of laminin-DG complexes. 30,31 Thus, it was of interest to investigate whether changes occur in the expression level of this molecule during renal tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Renal glomerular filtration apparatus is composed of three different components: The fenestrated endothelium, the glomerular basement membrane (GBM), and the epithelial cells with characteristic foot processes, known as podocytes (1)(2)(3)(4)(5)(6)(7)(8)(9). Filtration through this barrier depends on the charge and the size of the molecules present in the blood.…”
mentioning
confidence: 99%
“…This is highlighted by the experiments in which reactive oxygen speciesmediated disruption of the ␣-dystroglycan/matrix transmembrane complex led to a disordered organization of the fibrillar components of lamina rara externa as well as foot process effacement, which would conceivably result in detachment of the podocytes and ensuing proteinuria. 26 Such may be the case since neuraminidase-induced detachment in situ leads to increased permeability of ferritin ( Figure 3B). 27 This notion is further supported by the fact that its intravenous administration results in an increased urinary albumin excretion.…”
Section: Discussionmentioning
confidence: 99%